Web services to link interlibrary software with OCLC WorldShare. Issue 3 (19th August 2014) - Rodríguez-Gairín, Josep-Manuel; Somoza-Fernández, Marta
Abstract : Purpose: This article describes the use of web services to interconnect the GTBib interlibrary loan program with the OCLC WorldShare platform. Design/methodology/approach: We describe the current problem of duplication of procedures in libraries that have added their collections to the OCLC WorldCat catalogue in recent years and are therefore more likely to receive interlibrary loan requests through the WorldShare Platform. Findings: A solution that uses web services to insert and retrieve requests between the two systems is presented. Autonomous agents periodically check the status of the requests and keep them updated and synchronized. These agents also inform the library staff of any variation or inconsistency that is detected. Practical implications: This technology reduces process management time by making it unnecessary to introduce the request data in both systems. Agents are used to check the consistency of statuses between the two systems, thus avoiding errors and omissions and improving the efficiency of the whole interlibrary loan process. Originality/value: This paper describes in detail the technical aspects of the development as a reference for the development of future applications.